Order Trichoptera Kirby, 1813. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Holzenthal, Ralph W.; Morse, John C.; Kjer, Karl M. (Zootaxa, 2011)
-